Generalized Scheme for High Performing Photodetectors with a p‐Type 2D Channel Layer and n‐Type Nanoparticles. Issue 9 (18th December 2017) - Jia, Jingyuan; Jeon, Sumin; Jeon, Jaeho; Xu, Jiao; Song, Young Jae; Cho, Jeong Ho; Lee, Byoung Hun; Song, Jin Dong; Kim, Hyung‐Jun; Hwang, Euyheon; Lee, Sungjoo
Abstract: A generalized scheme for the fabrication of high performance photodetectors consisting of a p‐type channel material and n‐type nanoparticles is proposed. The high performance of the proposed hybrid photodetector is achieved through enhanced photoabsorption and the photocurrent gain arising from its effective charge transfer mechanism. In this paper, the realization of this design is presented in a hybrid photodetector consisting of 2D p‐type black phosphorus (BP) and n‐type molybdenum disulfide nanoparticles (MoS2 NPs), and it is demonstrated that it exhibits enhanced photoresponsivity and detectivity compared to pristine BP photodetectors. It is found that the performance of hybrid photodetector depends on the density of NPs on BP layer and that the response time can be reduced with increasing density of MoS2 NPs. The rising and falling times of this photodetector are smaller than those of BP photodetectors without NPs. This proposed scheme is expected to work equally well for a photodetector with an n‐type channel material and p‐type nanoparticles. Abstract : A generalized scheme for the fabrication of high performance photodetectors consisting of a p‐type channel material (black phosphorus) and n‐type nanoparticles (MoS2 ) is proposed, demonstrating enhanced photoresponsivity and detectivity compared to pristine black phosphorus photodetectors. It is found that the performance of hybrid photodetector depends on the density of nanoparticles on the black phosphorus layer.